Bio-Renewable Sources for Synthesis of Eco-Friendly Polyurethane Adhesives—Review - Gadhave, Ravindra V.; Mahanwar, Prakash A.; Gadekar, Pradeep T. (Scientific Research, 2017)
Bio-renewable sources used during manufacturing of polyurethane (PU) adhesives have been used extensively from last few decades and replaced petrochemical based PU adhesive due to their lower environmental impact, easy availability, low cost and biodegradability. Bio-renewable sources, such as vegetable oils (like palm oil, castor oil, jatropha oil, soybean oil), lactic acid, potato starch and other bio-renewable sources, constitute a rich source for the synthesis of polyols which are being considered for the production of “eco-friendly” PU adhesives. Various bio-renewable sources for synthesis of bio-based PU adhesives and their potential applications are discussed in this review. This paper will focus on the progress of research in bio-based materials for adhesive application.
Keywords: Bio-Renewable; Polyol; Oil; Polyurethane; Adhesive